2008
DOI: 10.1088/0957-4484/19/33/335603
|View full text |Cite
|
Sign up to set email alerts
|

Growth of one-dimensional Si/SiGe heterostructures by thermal CVD

Abstract: The first results on a simple new process for the direct fabrication of one-dimensional superlattices using common CVD chambers are presented. The experiments were carried out in a 200 mm industrial Centura reactor (Applied Materials).Low dimensionality and superlattices allow a significant increase in the figure of merit of thermoelectrics by controlling the transport of phonons and electrons. The monocrystalline nanowires produced according to this process are both one-dimensional and present heterostructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…[35][36][37][38] It was shown that in lattice-mismatched NW HJs, structural relaxation can be associated with defects in the form of twin boundaries parallel to the growth axis and directly related to the NW kinking. 35 Also, a rough NW surface typically indicates a high density of surface defects, 39 and in many cases the NW diameter continuously decreases producing so-called "tapered" NWs.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] It was shown that in lattice-mismatched NW HJs, structural relaxation can be associated with defects in the form of twin boundaries parallel to the growth axis and directly related to the NW kinking. 35 Also, a rough NW surface typically indicates a high density of surface defects, 39 and in many cases the NW diameter continuously decreases producing so-called "tapered" NWs.…”
Section: Discussionmentioning
confidence: 99%
“…By switching the doping precursor, doping profiles in axial direction can be created. [19][20][21][22] REVIEW www.advmat.de…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…Moreover, high carrier mobility exhibited by SiGe promotes the performance of devices. Various methods employing laser ablation , plasma enhanced‐CVD , and thermal CVD have been illustrated in the literature for the elaboration of such heterostructures. In case of catalyzed growth of hNWs, while switching the fluxes of gases, the catalyst acts as a reservoir leading to a graded transition region from residual atoms present in the catalyst, over a certain length.…”
Section: Introductionmentioning
confidence: 99%